"If [multiple myeloma] is just for Black people, they don't care to study it, maybe that's why it is no cure": Dyadic perspectives on the legacy of Tuskegee and trust in medical care for multiple myeloma. Issue 28 (1st October 2022) - Erisnor, Gabriell; Mills, Jiona A; Moore, Mykela; Bates-Fraser, Lauren C.; Mihas, Paul; Grant, Shakira Jeanene
Abstract : 177 Background: Older Black adults are disproportionately burdened by multiple myeloma (MM) yet continue to face significant challenges in accessing high-quality cancer care, including opportunities to engage in research. Knowledge of experiments such as the Tuskegee Study, where Black persons experienced deliberate harm from research, has created mistrust of the healthcare system, especially in the Black community. We sought to examine racial differences in dyadic (patient-informal caregiver) knowledge of the Tuskegee study and understand their perceptions of care received for MM. Methods: We conducted 21 in-depth semi-structured interviews with racially concordant patient-informal caregiver dyads living in North Carolina. Dyads were asked open-ended questions about the Tuskegee Study, mistrust, and their healthcare experiences. We used the Sort and Sift, Think and Shift approach for qualitative data analysis. Results: Between November 2021 and April 2022, we enrolled 44 participants [(mean age, patients: 70 years (range = 57-90), caregivers: 68 years (range = 37-88)], and interviewed 42 (11 Black and 10 White dyads). Fourteen (67%) dyads (6 White, 8 Black) reported knowledge of the Tuskegee Study. We identified Black-White differences in how this knowledge influenced perceptions about the care received for MM, including provider and healthcare system interactions, where Black dyads reported mistrust because of this knowledge (" if [MM] is just for Black people, they don't care to study it, maybe that's why it is no cure "). Conversely, most White dyads reported no impact of this knowledge on their current level of trust in the healthcare system and expressed their discomfort with discussing the Tuskegee Study and other events that led to the deliberate harm of Black persons. Black dyads stressed the persistent nature of racial injustice in the healthcare system, creating a shared consciousness within the Black community that "Black patients don't get the attention... the care, that [their] counterpart does." Black dyads emphasized the need for self-advocacy when interacting with providers and proactively sought to gain knowledge about their disease. Black and White dyads highlighted the importance of having a caregiver as an advocate, but Black dyads perceived caregiver presence as a potential mitigator of discrimination (" seeing a husband [and] wife, together. I think that makes a difference" ). Conclusions: Black dyads often expressed knowledge of the Tuskegee Study, the related legacy of mistrust in the healthcare system, the need for self-advocacy, and knowledge of the disease when interacting with providers. These factors, including transparent communication with providers and acknowledgment of drivers of mistrust, are critical for enhancing the care experiences of older dyads affected by MM.